Obesity and dental caries in young children in Plymouth, United Kingdom: A Spatial Analysis - Paisi, Martha; Kay, Elizabeth; Kaimi, Irene; Witton, Robert; Nelder, Robert; Christophi, Costas A.; Lapthorne, Debra (My University, 2018)
Objective: To examine the spatial clustering of obesity and dental caries in young children in Plymouth, United Kingdom, to evaluate the association between these conditions and deprivation, and explore the impact of neighbourhood-level characteristics on their distribution. Basic research design: Cross-sectional study analysing data from the National Child Measurement Programme (N=2427) and the Local Dental Health Survey (N=1425). The association of deprivation with weight status and caries was determined at individual and area level, using ANOVA and Poisson models. The overall spatial clustering was assessed using a modified version of the Global Moran's I, while clusters were located through Local Indicators of Spatial Association. Spatial autocorrelation was assessed using the variograms of the raw values. Log-linear Poisson models were fitted to assess the significance of neighbourhood characteristics on overweight/obesity and caries distribution. Results: At an individual level, deprivation was not associated with BMI z-scores but was a significant predictor of caries (p<0.05). However, at area level, deprivation related to the rates of both conditions. A significant positive autocorrelation was observed across neighbourhoods for caries. The variograms suggested spatial autocorrelations up to 2.5 km and 3 km for overweight/obesity and caries, respectively. Among several neighbourhood characteristics, the proportion of people on benefits was found to be a significant predictor of caries rates. Conclusions: Our results underline the importance of considering geographic location and characteristics of the broader environment when developing strategies to target obesity and caries.
Keywords: Obesity; Caries; Children; Inequalities; Socioeconomic factors; Geographic location